The Effects of L-Carnitine Supplementation During Concurrent Training on the Functional Capacities and Body Composition in Obese Men - Zahabi, Ghadir; Ilic, Vladimir; García-Ramos, Amador; Cokorilo, Nebojsa (Journal of Health and Allied Sciences NU, 2024)
Background Despite extensive research, the effects of L-carnitine supplementation in treating obesity are still unclear and equivocal. L-carnitine transports fatty acids into mitochondria for oxidation and is marketed as a weight loss supplement. The purpose of the present research is to investigate the efficacy of L-carnitine during concurrent training on the functional capacities and body composition in obese men.Methods Thirty nonactive, obese males (age = 37.2 ± 1.5 years; body mass index = 33.8 ± 2.5 kg/m2) participated in this research. The participants were randomly divided into three groups: experimental group 1 (EXP1)—concurrent training with L-carnitine supplementation; experimental group 2 (EXP2)—L-carnitine supplementation without training; and control group—without training or L-carnitine supplementation. Concurrent training was performed for 8 weeks, three sessions per week, with a training intensity ranging from 60 to 75% of the maximum heart rate reserve and one-repetition maximum. Both experimental groups were supplemented with 35 mg L-carnitine supplement per kilogram body weight. Various functional and body composition variables were collected at three time points (pre-test, mid-test, and post-test).Results A number of variables were significantly improved in EXP1 after 4 and 8 weeks (systolic blood pressure, maximal oxygen consumption, weight, body mass index, and one-repetition maximum) and only after 8-weeks (diastolic blood pressure, resting heart rate, percentage of body fat, and fat-free mass). No significant changes were observed for EXP2 and the control group.Conclusion L-carnitine supplementation, in conjunction with concurrent training, emerges as a highly effective approach for enhancing body composition and boosting functional capacities in obese adult men. Therefore, it is recommended that overweight male individuals integrate concurrent training into their regimen while taking L-carnitine.
Keywords: L-carnitine; Exercise Training; Body Composition; one-repetition maximum